Pengaruh Earning Per Share (EPS) dan Price Earning Ratio (PER) Terhadap Harga Saham Pada PT. Unilever Indonesia, Tbk - Nurul Ayu Safitri Fitri; Alwi Alwi (JUEB : Jurnal Ekonomi dan Bisnis, 2023)
This research aims to determine the effect of Earning Per Share (Eps) and Price Earning Ratio (Per) on share prices at Pt. Unilever Indonesia, Tbk. This type of research uses associative methods, with a quantitative approach. The data collection technique uses secondary data in the form of a Consolidated Financial Position Report, Profit and Loss Report and PT Financial Overview Report. Unilever Indonesia Tbk. In this study the population is 41 years. The sampling technique used purposive sampling, namely for 10 years from 2012-2021. And the data analysis techniques used are the classical assumption test, multiple linear regression analysis, correlation coefficient test, coefficient of determination test, and hypothesis testing (t test and f test). The research results show that Earning Pershare has a partially significant effect on share prices. Price Pershare Ratio has a partially significant effect on share prices. And simultaneously Earning PerShare and Price Earning Ratio simultaneously influence share prices.